Soul rebels: the Rastafari - Lewis, William F. (Waveland Press, 1993)
"Book-length monograph on the Rastafari uses both historical and participant observation ethnographic methods. Contains chapters on history of the movement, its adaptation to the urban area of Kingston, relationships with the Jamaican State, growth of Rastafari in the US, symbolism, problems with the law, and status of the social movement - or its evolution from charisma to institution"--Handbook of Latin American Studies, v. 57